KEMAMPUAN KOMUNIKASI MATEMATIS SISWA TUNAGRAHITA RINGAN SMALB-C NEGERI JEMBER DALAM MENYELESAIKAN SOAL PENJUMLAHAN DAN PENGURANGAN ALJABAR MENGGUNAKAN ALAT PERAGA KERTAS ALJABAR - Sholikhah, Mar’atus; Trapsilasiwi, Dinawati; Suharto, S; Susanto, S; Yudianto, Erfan (Kadikma, 2018)
Abstract. The purpose of this research is to describe the writing mathematical communication skills of mild mental retardation students at Jember State SMALB-C solved the problem of addition and subtraction of algebra using algebra paper learning media. The subject used are two students of class x mild mental retardation. Data collection are observation, test and interviews. Observation was carried out during the delivery of the addition and subtraction material of algebra and introducing learning media and giving practice questions. The question of test is algebra addition and subtraction as much as three reserved description and interview to each subject. The result of this research shows that subject has fulfilled of the indicators of NCTM's mathematical communication skills except sub indicator c in question number 2, because the student did not explain the algebra paper learning media attached to the answer sheet and do not write conclusions. In interview, the subject stated that using algebra paper learning media can help and simplify the problem of completing the addition and subtraction of algebra. Keywords: mild mental retardation student, mathematical communication skills, algebra paper learning media.